Filosopi Kearifan Lokal Tri Hita Karana Dalam Menjaga Kelangsungan Kelompok Wanita Tani “Jempiring” Kabupaten Badung - I Gusti Ayu Diah Yuniti; Anak Agung Ayu Rai Wahyuni; Anak Agung Rai Tirtawati; Ni Wayan Suryathi; I Gde Agoes Caskara Surya Putra (Jurnal Penelitian Agama Hindu, 2022)
This study aims to analyze the sustainability of the “Jempiring” Women Farmers Group, Badung Regency through the implementation of tri hita karana local wisdom. This study uses secondary data sources. The types of data include qualitative data. The data analysis technique is using qualitative analysis. Based on the results of the discussion, it can be concluded that the sustainability of the Women Farmers Group (KWT) "Jempiring" in Badung Regency is still running. This is due to the belief of the group members to continue to implement the local wisdom of tri hita karana in terms of parayangan, pawongan and palemahan. The implementation of various rituals (religious ceremonies) as a form of devotion to Ida Hang Hyang Widhi Waca, for the yadnya human ceremony, as well as for the implementation of the nyomia butha kala ceremony, continues.